Nilai Sosial Budaya Pancasila Dalam Tradisi Potong Gombak Kuncung: Studi Kearifan Lokal Di Desa Ngliman Kabupaten Nganjuk - Ramadhani, Aisyahrul; Andyastuti, Etty; Wiranata, Irawan Hadi (Lembaga Penelitian dan Pendidikan Mandala, 2026)
This study examines the social and cultural values of Pancasila embedded in the Potong Gombak Kuncung tradition in Ngliman Village, Nganjuk Regency, as well as the role of community leaders and traditional figures in preserving this tradition. This tradition is a unique hair-cutting ritual passed down through generations, containing noble values relevant to all five principles of Pancasila. The study employs a qualitative descriptive-phenomenological approach through observation, in-depth interviews, and documentation with four key informants. Results show that the tradition concretely implements the value of divinity through communal prayer, humanity through equal treatment and gotong royong, unity through collective ownership, democracy through deliberation mechanisms, and social justice through equitable participation. Traditional leaders serve as guardians of collective memory, while community leaders act as institutional drivers. This study affirms that local wisdom is a living manifestation of Pancasila values that existed long before Pancasila was formally established as the state foundation.